A COMPARATIVE REVIEW OF CLUSTERING AND CLASSIFICATION ALGORITHMS FOR BIG DATA ANALYTICS - Zogara, Lukas Umbu; Ningrum, Leny (Scientific Journal of Information System, 2025)
These days, there's so much data being created all the time. It’s honestly getting hard to keep up.That’s where data mining comes in. Basically, people use it to make sense of all this huge amount ofinformation, and there are two main ways to do it: clustering and classification. I found that there area bunch of algorithms for both, like K-Means, DBSCAN, and Hierarchical Clustering for clustering,and then there’s Decision Tree, Naïve Bayes, SVM, and Random Forest for classification. Each ofthese has its own strengths and weaknesses depending on the data you’re working with. The point ofthis paper was really to see how these algorithms perform and to give people an idea of which onemight work best depending on the situation. What we found is that no algorithm is perfect foreverything. So, choosing the right one really comes down to understanding the data and figuring outwhat you're trying to get out of it.